RELASI YAHUDI DAN NABI MUHAMMAD DI MADINAH : Pengaruhnya terhadap Politik Islam - Anwar, Khoirul (Al-Ahkam, 2016)
This paper describes how is the relationship between the Prophet Muhammad and the Jews of Medina reciprocally, as well as its influence on the political concepts that defined by the Prophet Muhammad. The political interests for the both relations cause the inception of harmony and disharmony state. The relation between the Prophet Muhammad and the Jews became different along with the changes of the desired political interests respectively. Besides that, the Jews in Medina had a lot of contribution to the Prophet Muhammad to realize the power stipulation stretched in all Arabian peninsula until he died. Although the prophet’s success is not entirely of the Jews, but the Jewish contribution may not be overlooked.